Hearing loss, depression, and medical service utilization among older adults: evidence from China. (April 2022) - Guan, Liding; Liu, Qing; Chen, Deshan; Chen, Chen; Wang, Zengwen
Abstract: Objectives: To acquire a better understanding of the mechanisms underlying the association between hearing loss and medical service utilization, this study examined the relationship between hearing loss, depression, and medical service utilization. Study design: Using the methods of probability proportional to size, a survey conducted in 28 provinces, 150 countries/districts, 450 villages/urban communities, 11, 628 households, and 19, 816 individuals of China in 2018. Methods: The data for this article were derived from the 2018 China Health and Retirement Longitudinal Study, which enrolled 14, 455 people aged 50–80 years. Hearing loss was determined using self-reported hearing status. Self-reported outpatient visits in the last month and hospitalization within the last year were used to determine medical service utilization. Depression was obtained from the CES-D-10 scale. Logistic regression and stepwise regression methods were used. Results: Older adults with hearing loss problems used significantly more outpatient care services (odds ratio [OR] = 1.292, 95% confidence interval [CI] 1.152, 1.449; P  < 0.001) and inpatient care services (OR = 1.238, 95% CI 1.021, 1.501; P  < 0.05) than those without hearing loss problems. Following that, individuals with hearing loss problems were more likely to experience depressive symptoms (OR = 1.467, 95% CI 1.345, 1.599; P  < 0.001) than those without. Moreover, respondents with depressive symptoms used outpatient care services at a significantly higher rate (OR = 1.292, 95% CI 1.152, 1.449; P  < 0.001) and inpatient care service at a significantly higher rate (OR = 1.238, 95% CI 1.021, 1.501; P  < 0.05) compared with those without depressive symptom. Conclusion: This article discovered that depression acted as a mediation variable in the relationship between hearing loss and medical service utilization. This research provided possible interventions for reducing the burden of the healthcare system and society that older adults with hearing loss imposed.